MEKANISME PENETAPAN NOMOR URUT CALON LEGISLATIF DPRD PROVINSI RIAU DAERAH PEMILIHAN KOTA PEKANBARU TAHUN 2014 (STUDI KASUS PADA PARTAI PERSATUAN PEMBANGUNAN) - Hanafi Saputra; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Political parties today is conducted openly at the crawl stage but in the selection of candidates and their establishment of Political Parties that do tend to be closed. Political parties only involve a number of elite administrators regional level without involving the participation of the community in the form of opportunities for the public to participate in assessing candidates to be promoted, as is known by consensus agreement of the Chairman of DPW PPP PPP Number: 074 / PPP.IX / NO.URUT / 2012 on Technical Guidelines for Determination of Number of Riau Provincial Council Member Candidates PPP it is known in article 3, said determination sequence number of candidates in the set based on the position and the positions in the party organization and further discussed in the Congress Party, the next can be seen in the following table Candidate name DPRD Pekanbaru based Dapil I Pekanbaru. To find out how the mechanism penetepan serial number by the United Development Party Determination of the serial number of candidates for legislators Riau Province of PPP it is done by way of deliberation and consensus which seuanya carried out according to the rules, among others, as contained in article 3 of the Technical Guidelines for the Determination of Number of Candidates Riau Provincial Assembly Members Keywords: Mechanisms, Determination, Serial Number, Legislative Candidates